2015
DOI: 10.1007/s13277-015-3649-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting increased copper levels in diethylnitrosamine induced hepatocellular carcinoma cells in rats by epigallocatechin-3-gallate

Abstract: We have earlier elucidated a pathway for the anticancer action of plant polyphenolic compounds against malignant cells involving mobilisation of endogenous copper ions and the consequent prooxidant action. To further confirm our hypothesis in vivo, we induced hepatocellular carcinoma (HCC) in rats by diethylnitrosamine (DEN). We show that in such carcinoma cells, there is a progressive elevation in copper levels at various intervals after DEN administration. Concurrently with increasing copper levels, epigallo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 46 publications
2
13
0
2
Order By: Relevance
“…In A549 xenografts of nude mice, EGCG could significantly inhibit the expression of HIF‐1α and VEGF protein, and suppress HIF‐1α‐dependent angiogenesis induced by nicotine, implying it could be a promising agent for prevention and treatment of smoking‐associated NSCLC . Interestingly, EGCG could induce DNA breakage in a pro‐oxidant manner by mobilizing endogenous copper ions to accumulate in HCC cancer cells and human peripheral lymphocytes, which has been confirmed by the investigation in the HCC rats induced by diethylnitrosamine . Additionally, EGCG was capable of inhibiting both initiation and progress of cellular carcinogenesis induced by the chemical carcinogen (2‐amino‐1‐methyl‐6‐phenylimidazo[4,5‐b]pyridine, PhIP) in mammary gland of nude mice via the suppression of Ras‐ERK‐NOX‐ROS signaling pathway .…”
Section: Anticancer Activities and Potential Mechanismsmentioning
confidence: 73%
See 1 more Smart Citation
“…In A549 xenografts of nude mice, EGCG could significantly inhibit the expression of HIF‐1α and VEGF protein, and suppress HIF‐1α‐dependent angiogenesis induced by nicotine, implying it could be a promising agent for prevention and treatment of smoking‐associated NSCLC . Interestingly, EGCG could induce DNA breakage in a pro‐oxidant manner by mobilizing endogenous copper ions to accumulate in HCC cancer cells and human peripheral lymphocytes, which has been confirmed by the investigation in the HCC rats induced by diethylnitrosamine . Additionally, EGCG was capable of inhibiting both initiation and progress of cellular carcinogenesis induced by the chemical carcinogen (2‐amino‐1‐methyl‐6‐phenylimidazo[4,5‐b]pyridine, PhIP) in mammary gland of nude mice via the suppression of Ras‐ERK‐NOX‐ROS signaling pathway .…”
Section: Anticancer Activities and Potential Mechanismsmentioning
confidence: 73%
“…To further investigate the antitumor activity of EGCG in vivo, several animal models have been developed including A549 xenografts of nude mice, HCC in rats, orthotopic colon cancer in nude mice, and so on. In A549 xenografts of nude mice, EGCG could significantly inhibit the expression of HIF‐1α and VEGF protein, and suppress HIF‐1α‐dependent angiogenesis induced by nicotine, implying it could be a promising agent for prevention and treatment of smoking‐associated NSCLC .…”
Section: Anticancer Activities and Potential Mechanismsmentioning
confidence: 99%
“…Kasprzak et al () and Rizvi, Rizvi, and Naseem () reported that anticancer activities could be enhanced when flavonoids form a complex with transition metal ions. Numerous studies show that transition metal concentration is higher in serum of various cancer subjects and also at cancer bearing site (Eagon et al, ; Farhan, Rizvi, Naseem, Hadi, & Ahmad, ). Therefore, in the present study, we selected biologically active transition metal ions such as Cu, Zn, and Fe to complex with TXER.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, the effect of the apoptotic mechanism stimulated by lower mitochondrial membrane potential and the G0/G1 phase cell cycle arrest was previously demonstrated in HCC. 25 In addition, other reports have indicated that targeting the EP(1) receptor 26 and copper accumulation 27 can mediate anti-HCC activities. In our study, EGCG at concentrations below 50 μ M could inhibit HepG 2 cell growth slightly better than higher EGCG concentrations of 50–100 μ M under the same conditions ( Figure 1a ).…”
Section: Discussionmentioning
confidence: 96%